Intermolecular steric inhibition of Ephexin4 is relieved by Elmo1 - Kwanhyeong Kim (Nature Portfolio, 2017)
Abstract Ephexin4, a guanine nucleotide-exchange factor for RhoG, promotes engulfment of apoptotic cells and cancer cell migration in a RhoG-dependent manner, which is synergistically augmented by Elmo1, an Ephexin4-interacting protein. However, the underlying molecular mechanism remains elusive. Here, we report a mechanism by which Elmo1 cooperates with Ephexin4 to activate RhoG. We found that Ephexin4 activity was increased by elimination of its SH3 domain which intermolecularly interacts with the N20 region of Ephexin4. This interaction prevented RhoG from binding to Ephexin4 and thus inhibited RhoG activation. Moreover, we also found that Elmo1 associated with the SH3 domain as well as the N20 region and competed with the SH3 domain for binding to the N20 region, interrupting the interaction of the SH3 domain with the N20 region and thereby promoting RhoG binding to Ephexin4. In addition, the activity of Ephexin4 lacking the SH3 domain was comparable to that of Ephexin4 with Elmo1. Taken together, the data suggest that Elmo1 relieves the steric hindrance of Ephexin4 generated by the intermolecular interaction of the SH3 domain and makes Ephexin4 more accessible to RhoG.